2019
DOI: 10.1139/cjfr-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant-derived smoke water and potassium nitrate on germination of understory boreal forest plants

Abstract: This experiment assessed the effects of plant-derived smoke water, potassium nitrate (KNO3), and their combined effect on germination of cold-stratified and non-stratified seed from 18 native boreal forest plant species. Seeds were treated with smoke water diluted to 1:20, 0.1% KNO3, and smoke water + KNO3. Nine species responded positively to smoke water; these responses were dependent on the type of stratification, and three of these species only had a positive response to smoke water + KNO3 solution. Five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, several studies have revealed the regulation of seed dormancy (or germination) by temperature is involved in the change in the sensitivity of seed germination to nitrate. For example, the sensitivity of seeds to nitrate increased after D r a f t seeds were treated with cold stratification (Bouwmeester et al 1994;Mackenzie and Naeth 2019). For seeds buried in soil, nitrate sensitivity changed during the dormancy cycle, driven by seasonal temperature (Bouwmeester et al 1994;Finch-Savage and Footitt 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have revealed the regulation of seed dormancy (or germination) by temperature is involved in the change in the sensitivity of seed germination to nitrate. For example, the sensitivity of seeds to nitrate increased after D r a f t seeds were treated with cold stratification (Bouwmeester et al 1994;Mackenzie and Naeth 2019). For seeds buried in soil, nitrate sensitivity changed during the dormancy cycle, driven by seasonal temperature (Bouwmeester et al 1994;Finch-Savage and Footitt 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This trend may be due to the quantity and quality of fuel available to historic fires, potentially preventing severe combustion of the organic horizon and limiting belowground carbon stock losses at fire-origin sites. Alternatively, these trends may be due to common boreal post-harvesting practices, which can also reduce belowground stocks by actively relocating or removing post-harvest organic soils (Colombo, Parker, Luckai, Dang, & Cai, 2005;Frey, Lieffers, Munson, & Blenis, 2003). Site preparation techniques remove surface soils from the forest floor at large to limit competition from less profitable species, while generating microclimate conditions that can enhance the productivity of target tree species (Frey et al, 2003).…”
Section: Legacy Effects Of Human Land Use On Contemporary Carbon Dymentioning
confidence: 99%
“…Seed germination test (Mackenzie and Naeth, 2019): full, unbroken seeds of C. pilosula were selected. Seeds were soaked in distilled water for 6 h before the test, then surface-sterilized with 5% sodium hypochlorite solution for 15 min, and then rinsed several times with sterile water.…”
Section: Seed Germination Testmentioning
confidence: 99%